Missing data and other challenges in assessing inappropriate marketing of baby foods in the Russian Federation: a cross-sectional study - Qi Chen; Kremlin Wickramasinghe; Holly L Rippin; Anna Kontsevaya; Oxana Drapkina; Suqi Lyu; Dinara Mukaneeva; Aleksandra Antsiferova; Melita Vuknovic (BMJ Open, 2023)
Objectives We used the WHO draft nutrient profile model (NPM) to evaluate baby foods targeted at infants and young children (IYC) aged 6–36 months in the Russian Federation to assess their suitability for marketing.Design A cross-sectional study in Moscow (Russian Federation).Setting Nutrition information of baby food was primarily collected from retailer websites, with some complementary data from physical stores. Both specialist stores for IYC and general supermarkets were included.Participants Two hundred and thirty baby food products targeted to IYC were selected. Breastmilk substitutes and products targeted at children over 3 years old were excluded.Main outcome measures Per cent of missing nutrition data, per cent of products with added sugar or sweetener and exceeded sodium or salts, per cent of products marketed as suitable for IYC under 6 months.Results Most products were ‘ready-to-eat’, including fruit (n=42, 18.5%) and vegetable (n=29, 12.8%) purees, meat, fish or cheese purees (n =26, 11.5%); ‘dry or instant cereal/starchy foods’ (n=27, 11.9%), including predominantly dry cereals, ‘juices and other drinks’ (n=26, 11.5%). 95% (n=219/230) of products were missing total sugar information, 78% (n=180/230) were missing either sodium or salt, and 25% (n=57/230) were missing total fat. Among products with sugar and sodium information, 41% (n=94/230) included added sugar or sweeteners, and 48% (n=24/50) exceeded the NPM sodium threshold. 40% of products (n=92/230) were marketed as suitable for IYC aged under 6 months.Conclusion Baby foods marketed for IYC showed a high per cent of missing nutrition information and disparity with WHO’s guidelines for complementary feeding, age of introduction, sugar and salt content. Stronger regulation is needed in this area to minimise higher risk of non-communicable diseases (NCDs) in later life.